2011
DOI: 10.1051/0004-6361/201117120
|View full text |Cite
|
Sign up to set email alerts
|

The Galactic dust-to-metals ratio and metallicity using gamma-ray bursts

Abstract: The metallicity and dust-to-metals ratio of the Galaxy are fundamental parameters in understanding the interstellar medium (ISM). Currently, there is still some uncertainty surrounding these parameters. In this paper, the dust-to-metals ratio in the Galaxy is determined using the photoelectric absorption of the soft X-ray afterglows of a large sample of several hundred gamma-ray bursts (GRBs) to determine the metal column density in combination with Galactic dust maps to determine the line-of-sight dust extinc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 40 publications
6
112
1
Order By: Relevance
“…For the BG components, we fixed all the parameters at the values in Table 2, except for the absorbing column density, which we reduced from N H ∼ 1 × 10 22 cm −2 (Table 3) to N H = 0.7 × 10 22 cm −2 . This is because our spectral extraction region is located within the absorption hole, where the visual extinction A V is ∼1.5 mag less than that in the surrounding region (Sano et al 2015), which is equivalent to ∆N H = 3×10 21 cm −2 , according to the N H -A V relation, N H = 2.2 × 10 21 cm −2 A V mag (Gorenstein 1975;Watson 2011). The N H value we employed is consistent with that measured for the CCO, ∼ 0.7 × 10 22 cm −2 (Cassam-Chenaï et al 2004).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…For the BG components, we fixed all the parameters at the values in Table 2, except for the absorbing column density, which we reduced from N H ∼ 1 × 10 22 cm −2 (Table 3) to N H = 0.7 × 10 22 cm −2 . This is because our spectral extraction region is located within the absorption hole, where the visual extinction A V is ∼1.5 mag less than that in the surrounding region (Sano et al 2015), which is equivalent to ∆N H = 3×10 21 cm −2 , according to the N H -A V relation, N H = 2.2 × 10 21 cm −2 A V mag (Gorenstein 1975;Watson 2011). The N H value we employed is consistent with that measured for the CCO, ∼ 0.7 × 10 22 cm −2 (Cassam-Chenaï et al 2004).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…where DTM LG ≡ 10 −21.3 mag cm 2 is the DTM in the Local Group (Watson 2011). Recently, Zafar & Watson (2013), using different classes of objects, found that DTM is independent of galaxy type or age, redshift, or metallicity and is very close to the value in the Local Group.…”
Section: Dust-to-metals Ratiomentioning
confidence: 91%
“…The pixel scale is 5 × 5 , resulting in a pixel area of A pix = 1.26 × 10 32 cm 2 at an assumed distance of 150 pc. The conversion factor of N H /A V = 2.2 × 10 21 cm −2 mag −1 (Ryter 1996;Güver & Özel 2009;Watson 2011) was applied. Then we extracted the source from this map via a 2D Gaussian fit after an unsharp masking procedure by convolving the original extinction map to three resolutions, 30 , 40 and 50 .…”
Section: Morphologymentioning
confidence: 99%
“…For a more recent characterisation of that ratio (Ryter 1996;Güver & Özel 2009;Watson 2011), the numerical value in this conversion is modified by about 18%. To be able to convert the quoted ratio N H /A V to N H /E B−V , we have assumed R V = 3.1 as the mean value for the diffuse ISM, and replaced the corresponding ratio in the equation above:…”
mentioning
confidence: 99%